Forequarter amputation in a patient with locally advanced recurrent breast carcinoma - Vieira, René Aloisio da Costa; Toller, Eduardo Areas; Morgan, Andréa Moreno; Oliveira-Junior, Idam de (Mastology, 2020)
Forequarter amputation (FQA) involves the removal of the upper limb, clavicle, and scapula and is indicated for the resection of primary or metastatic tumors invading the axillary neurovascular bundle. Reports on breast cancer have associated FQA with the primary resection of a locally advanced tumor, resection of recurrent disease, brachial plexus injury, Stewart-Treves syndrome, or sarcoma secondary to breast cancer irradiation. We described a case of recurrent breast carcinoma with curative-intent surgery. The surgery aimed at locoregional control and improvement in the quality of life. The literature is scarce on the topic, discussing the multiple aspects related to the indication of FQA for breast cancer patients. This report presents the first case described in Latin American literature.